Experimental research on the chlorine salt corrosion resistance of alkali activated low-carbon concrete - Xu, Shaoyun; Tang, Jianzhong; Wang, Limin (Frontiers in Materials, 2024)
This paper presents orthogonal experiments to investigat the effects of sol ratio, content of fly ash and slag, expander and modulus of sodium silicate on the chlorine salt corrosion resistance of alkali activated low-carbon concrete (AALC). The microstructures and product compositions of AALC after chloride ion erosion were further analyzed by Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). The results show that with an increase of sol ratio, the color depth of AALC gradually increases at 28 days, but the growth trend slows down, the difference of unsteady migration coefficient between sol ratio of 0.44 and 0.46 at 28 days is not obvious, and the unsteady migration coefficient increases first and then decreases at 56 days. As the fly ash content increases, the color depth of AALC increases significantly, when the fly ash content is 10%, it increases by 28.92% compared with AALC without fly ash, and when the fly ash content is 20%, it increases by 27.10% compared with that of 10%. With an increase of fly ash content, the unsteady migration coefficient gradually increases at 14, 28 and 56 days, when the fly ash content is 10%, it increases by 60.66% compared with AALC without fly ash, and when the fly ash content is 20%, it increases by 78.57% compared with that of 10%. As the content of expander increases, the color depth of AALC shows a trend of first decreasing and then increasing, the unsteady migration coefficients of 14, 28 and 56 days all increases first and then decreases. As the modulus of sodium silicate (Ms) increases, the color depth of AALC at 28 days decreases first and then increases, the unsteady migration coefficients at 14, 28 and 56 days all decreases first and then increases. In the process of sodium chloride solution soaking, the solution enters the internal pores of AALC, and unhydrated slag and fly ash will further react with sodium chloride to generate new hydration product of C-A-S-H. The hydration degree of AALC increases, and the internal structure becomes denser, corresponding to the peak value of hydration product C-S-H gel increases.